THE DEVELOPMENT OF POLITICAL THOUGHT IN AFRICA - Dr. Alier,; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Political Thought is divided into three general areas of study. The first looks at the history of political thought. This historical aspect of political thought is itself divided into three periods, with three basic Concentrations. The major periods are ancient, medieval, and modern and the three Concentrations are Western, oriental and Korean.Population is a subset of the target population and is also known as the study population. The accessible population is the population in research to which the researchers can apply their conclusions; it is from the accessible population that researchers draw their samples. The survey population that was researched on included; Technical staff (40), which comprised of Technocrats of SPLM Party, focal person, administrators like public relation officers, political experts and some support staff, twenty (20) beneficiaries of SPLM Party in the Republic of South Sudan.Most of the participants who responded ‘Yes’ constituted lion share of 72.9% while those who said ‘No’ that the current government of Transitional Government of National Unity (TGoNU) does not encourage the development of political thought made up 27.1% of the respondents. According to majority point of views, the current government of TGoNU has been playing a significant roles in encouraging the development of political thought in the country. And according to results, 62.5% said ‘Yes’ the current political parties support the development of polities though in the country while 37.5% presents those who opposed the statement due to their owns perception of the current political parties’ activities this concurred with sultan Yosa Wawa who said in a conference that political parties support the development of political policiesIt was shown that 87.5% majority of participants responded ‘Yes’ they think the people have the right to organize in different political parties or other competitive political groupings of their choice in support of political thought however, 12.5% among participants said ‘No’. The statement is proven to correct by majority of the respondents who have agreed with it. In other hand, 52.1% said ‘No’, there is no a realistic opportunity for the political parties in South Sudan to build the political ideology while 47.9% of participants responded ‘Yes’ there is a space for political parties to establish political ideology. Based on the finding results, majority of the respondents were politically frustrated and hence they don’t see any ground of establishing a beneficial political ideology due poor political ideals developed in the country